Development of cellular absorptive tracers (CATS) for a quantitative characterization of microbial mass in flow systems - Choi, Jaeyoung; Saripalli, Prasad; Meldrum, Deirdre; Lee, Ju Young (ELSEVIER SCI LTD, 2007)
A new method was developed for a simple non-destructive characterization of bacterial mass in flow systems. Results of partition and transport experiments showed that adsorption of a CAT molecule into the cellular mass resulted in its retardation during flow, which was a good measure of the biomass quantity and distribution. Three dyes, acridine orange (AO), toluidine blue (TB), and safranin O (SO), were chosen as CATs to demonstrate their utility to quantitatively characterize the biomass, its location and morphology in flow system. The results clearly demonstrated the applicability of AO, TB, and SO as cellular absorptive tracers in columnar flow experiments. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: POROUS-MEDIA; TRANSPORT